The Past, Present, and Future of the Restatement of Copyright - Balganesh, Shyamkrishna; Ginsburg, Jane C. (The Columbia Journal of Law & the Arts, 2021)
It is now six years since the American Law Institute (ALI) began work on its first ever Restatement of an area dominated by a federal statute: copyright law. To say that the Restatement of the Law, Copyright (hereinafter “Restatement”) has been controversial would be a gross understatement. Even in its inception, the ALI identified the project as an outlier, noting that it was likely to be seen as an “odd project” since copyright “is governed by a detailed federal statute.”1 Neither the oddity nor the novelty of the project, however, caused the ALI to slow its efforts to push the project forward, and despite the persistence of serious objections from within the membership of the project (including many of the project’s Advisers), the first draft of the Restatement is scheduled to go to a vote seeking adoption by the organization’s full membership in the middle of 2021.